Prodorne in preroške misli 16. stoletja: ob petstoletnici Trubarjevega rojstva - Bošnjak, Blanka (Slavia Centralis, 2020)
Penetrating and Prophetic Thoughts of the 16th century: on the five-hundredth anniversary of the Trubar's birth
Keywords: scientific conference; five-hundredth anniversary of the Trubar's birth; Slovenian protestants; protestantism; 16th century